CZY UPOKARZANIE JEST „WSZECHOBECNE"? - Iwona Kabzińska (Etnografia Polska, 2013)
Making a reference to Andrzej Szahaj s and Michał Rydłewski s reflections on the culture of humiliation, present for instance in many popular TV shows, the Author points out another areas dominated by this phenomenon. These are schools, health service institutions (mostly public), nursing houses for elders and chronically sick people. Humiliation is being experienced by people at work, those who look for a job or even in families. Humiliation of individuals and groups often is publicized by médias. It preserves a one-dimension, negative image of Polish society created by médias. It says relatively little about Polish successes and activities aimed at fight against humiliation (and in most cases boorishness). Szahaj and Rydłewski argue that culture of humiliation is a significant element of neoliberal model of society, present also in Poland. What is more important, it is generally accepted. That is why Author is skeptical about positive changes at schools, in health care institutions or - generally - in social relations.